2019
DOI: 10.1002/1873-3468.13497
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of amyloid‐induced toxicity by ergothioneine in a transgenic Caenorhabditis elegans model

Abstract: The abnormal accumulation of β‐amyloid peptide (Aβ) is recognized as a central component in the pathogenesis of Alzheimer disease. While many aspects of Aβ‐mediated neurotoxicity remain elusive, Aβ has been associated with numerous underlying pathologies, including oxidative and nitrosative stress, inflammation, metal ion imbalance, mitochondrial dysfunction, and even tau pathology. Ergothioneine (ET), a naturally occurring thiol/thione‐derivative of histidine, has demonstrated antioxidant and neuroprotective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…Probably such antioxidant activities are at the core of its biological benefits. Caenorhabditis elegans Protection from amyloid-β-induced cell death (521) Cell injury Rat pheochromocytoma cells Methylglyoxal challenge (573) Cell proliferation K562 cells Involvement of SLC22A4 (418) Caco-2 cells Involvement of SLC22A4 (429) Diabetic embryopathy Rats ERG reduced it to control levels (574) DNA damage in mitochondria HeLa, RAW 264•7, HaCaT, PC12 cells siRNA knockdown of SLC22A4…”
Section: The Biology Of Ergothioneinementioning
confidence: 99%
See 2 more Smart Citations
“…Probably such antioxidant activities are at the core of its biological benefits. Caenorhabditis elegans Protection from amyloid-β-induced cell death (521) Cell injury Rat pheochromocytoma cells Methylglyoxal challenge (573) Cell proliferation K562 cells Involvement of SLC22A4 (418) Caco-2 cells Involvement of SLC22A4 (429) Diabetic embryopathy Rats ERG reduced it to control levels (574) DNA damage in mitochondria HeLa, RAW 264•7, HaCaT, PC12 cells siRNA knockdown of SLC22A4…”
Section: The Biology Of Ergothioneinementioning
confidence: 99%
“…Note, however, that at least one mushroom trial indicated no measurable benefits in healthy young physical education students (514) . Brain and serum ERG levels are also markedly different in Parkinson's disease (515) , reviewed in Hang et al (516) , Shao & Le (517) and Shah & Duda (518) , and even in sudden infant death syndrome (519) , and ERG has been shown to be protective against β-amyloid-induced neuronal injury (520) and cytotoxicity (521) . It can also act as an antidepressant (522) .…”
Section: Neurological Diseases and Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have suggested that ET is preferentially accumulated in tissues predisposed to oxidative stress and inflammation and may even be concentrated at sites of tissue injury by cellular modulation of the levels of OCTN1 [ 24 , 32 , 56 , 57 ]. These unique capabilities of ET, which have been reported in a wide range of studies in cells, animal models, and also population studies, suggest that the cytoprotective abilities of ET may be helpful against disorders such as dementia [ 58 , 59 , 60 ], depression [ 61 ], atherosclerosis [ 45 , 46 ], cardiovascular disorders [ 46 , 62 , 63 , 64 ], nonalcoholic fatty liver disease [ 56 ], preeclampsia [ 65 , 66 ], ischemia-reperfusion injury [ 39 , 50 , 67 ], and, especially relevant in this case, ARDS [ 68 ]. This list is by no means exhaustive, with new applications for ET constantly being identified even in other areas of human health, such as improving the efficacy of cancer vaccines [ 69 ] and protection against chemotherapy-induced peripheral neuropathy [ 70 ].…”
Section: Biology Of Ergothioneinementioning
confidence: 99%
“…ET has been shown to be protective against a range of neurotoxins in both in vitro and in vivo models, such as amyloid-β [ 58 , 59 , 183 ], cisplatin [ 184 ], D-galactose-induced dementia [ 185 ], and N -methyl-D-aspartate-induced cytotoxicity in rat retinal neurons [ 186 ]. Moreover, preclinical studies have revealed that ET preserved dopaminergic neurons and motor function in a 6-hydroxydopamine murine model of PD (manuscript in preparation).…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%